Hubungan Kepatuhan Oral Hygiene terhadap Kejadian Mukositis pada Remaja dengan Kanker yang Menjalani Kemoterapi di Rumah Sakit Kanker Dharmais Jakarta Tahun 2022 - Restika Chitra; Yuni Susilowati; Alfika Safitri (Pusat Riset dan Inovasi Nasional, 2024)
Chemotherapy causes side effects, including mucositis. As an effort to prevent the occurrence of mucositis, namely by cleaning the mouth area properly and correctly, including doing oral hygiene. The results of a preliminary study on 10 adolescents found that 7 of them had mucositis. The relationship between oral hygiene adherence to the incidence of mucositis in adolescents with cancer undergoing chemotherapy at the Dharmais Cancer Hospital Jakarta in 2022. Quantitative analysis with a cross sectional design. The sample size of this study was 140 with accidental sampling technique. Data analysis using Chi Square Test. Most of the adolescents adhered to oral hygiene 58.6% and experienced mucositis with a mild degree of 58.6%. There is a relationship between oral hygiene adherence to the incidence of mucositis in adolescents with cancer undergoing chemotherapy at the Dharmais Cancer Hospital, Jakarta, with p = 0.000. There is a relationship between oral hygiene adherence to the incidence of mucositis in adolescents with cancer undergoing chemotherapy. Adolescents are expected to be able to apply the knowledge that has been obtained, routinely carry out periodic checks every 6 months at the dentist, and immediately consult a doctor if complaints occur in the oral cavity so as not to experience mucositis with a more severe degree.